Clustering with JWST: Constraining galaxy host halo masses, satellite quenching efficiencies, and merger rates at z = 4−10. Issue 1 (4th February 2020) - Endsley, Ryan; Behroozi, Peter; Stark, Daniel P; Williams, Christina C; Robertson, Brant E; Rieke, Marcia; Gottlöber, Stefan; Yepes, Gustavo
ABSTRACT: Galaxy clustering measurements can be used to constrain many aspects of galaxy evolution, including galaxy host halo masses, satellite quenching efficiencies, and merger rates. We simulate JWST galaxy clustering measurements at z ∼ 4–10 by utilizing mock galaxy samples produced by an empirical model, the universemachine . We also adopt the survey footprints and typical depths of the planned joint NIRCam and NIRSpec Guaranteed Time Observation program planned for Cycle 1 to generate realistic JWST survey realizations and to model high-redshift galaxy selection completeness. We find that galaxy clustering will be measured with ≳5σ significance at z ∼ 4–10. Halo mass precisions resulting from Cycle 1 angular clustering measurements will be ∼0.2 dex for faint (−18 ≳ $M_{UV}^{ }$ ≳ −19) galaxies at z ∼ 4–10 as well as ∼0.3 dex for bright ($M_{UV}^{ }$ ∼ −20) galaxies at z ∼ 4–7. Dedicated spectroscopic follow-up over ∼150 arcmin 2 would improve these precisions by ∼0.1 dex by removing chance projections and low-redshift contaminants. Future JWST observations will therefore provide the first constraints on the stellar–halo mass relation in the epoch of reionization and substantially clarify how this relation evolves at z > 4. We also find that ∼1000 individual satellites will be identifiable at z ∼ 4–8 with JWST, enabling strong tests of satellite quenching evolution beyond currently available data ( z ≲ 2). Finally, we find that JWST observations can measure the evolution of galaxy major merger pair fractions at z ∼ 4–8 with ∼0.1–0.2 dex uncertainties. Such measurements would help determine the relative role of mergers to the build-up of stellar mass into the epoch of reionization.